PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA CV HUGO PRIMA RAYA KABUPATEN TANGERANG - Kintan Cahya Abdih; Irma Sari Octaviani (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This study aims to determine the influence of organizational culture and job satisfaction on employee performance both partially and simultaneously at CV Hugo Prima Raya Tangerang Regency. This research method uses a quantitative research method with an associative method approach. The data collection method used is primary data and secondary data. The population in this study was 113 employees, the sampling technique used was slovin, namely 54 respondents. Data analysis used SPSS version 25 Data collection by questionnaire. The data analysis method uses validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedasticity test, auto correlation test, multiple linear regression analysis, correlation coefficient test, determination coefficient test, and hypothesis test. The results of the study show that: (1) Partial hypothesis testing of the organizational culture variable (X1) obtained a calculated t-value> t-table (9.201> 2.006) and a significance value of 0.000 <0.05, meaning that Organizational Culture (X1) has a positive and significant effect on Employee Performance (Y). (2) Partial hypothesis testing of the Job Satisfaction variable (X2) obtained a calculated t-value > t-table (7.671 > 2.006) and a significance value of 0.000 < 0.05, meaning that Job Satisfaction (X2) has a positive and significant effect on Employee Performance (Y). (3) Simultaneous hypothesis testing obtained a calculated f-value > f-table (67,370 > 3.18) and a significance value of 0.000 < 0.05, it can be concluded that Organizational Culture (X1) and Job Satisfaction (X2) have a positive and significant effect simultaneously on Employee Performance (Y). The determination obtained R Square of (0.725) means that the variables of Organizational Culture and Job Satisfaction together have a contribution of (72.5%) influence on Employee Performance. While the remaining (27.5%) is influenced by other factors not examined in this study. Keywords: Organizational Culture, Job Satisfaction, Employee Performance